The Potential of UIN Prof. KH. Saifuddin Zuhri in the Development of the Halal Industry in Purbalingga Regency - Riyadi, Sugeng (Mabsya: Jurnal Manajemen Bisnis Syariah, 2023)
This paper aims to reveal the regional orientation of Purbalingga district, Central Java. In terms of the urgency of the presence of tertiary institutions, in order to strengthen the halal industry, The research uncovers the meta-potential of resources involving regional planning, socio-economic, religious, regulatory, and educational volumes. This research is based on observational qualitative research with an administrative data approach and field research. As a result, it was found that the development of the halal industry in Purbalingga district was relatively new. With the initiation of the presence of a number of supporting government institutions, both in the field of religion and strengthening business actors. With the industrialization policy, the presence of relevant tertiary institutions is increasingly needed to be it. In this case, it is necessary to ratify halal industry regulations to accommodate the implementation of the development and strengthening of the halal industry. Local governments must accelerate the halal industry by strengthening programs for all elements of society, academics and religious leaders. The implementation of Islamic Higher Education in the development of the halal industry in Purbalingga Regency must get a priority in an effort to build development and human indexes in addition to strengthening industrial areas.